2021
DOI: 10.1001/jamanetworkopen.2021.9382
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Morbidity of Infants Born Extremely Preterm at Tertiary Medical Centers in China From 2010 to 2019

Abstract: This cohort study examines the association of preterm birth with risk of mortality and morbidity among infants born in China from 2010 to 2019.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 48 publications
(89 reference statements)
4
55
1
1
Order By: Relevance
“…We found that preterm infants admitted to NICUs in eastern China were at the lowest risks of death, whereas infants in western China had the highest mortality. Several studies have reported a similar disparity of maternal, child, and neonatal mortality from eastern to western China (1)(2)(3)(20)(21)(22)(23). Overall, inadequate health service infrastructures and low health expenditure due to less developed economic status are thought to have resulted in inequity in neonatal and child health in the western region (2,23).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We found that preterm infants admitted to NICUs in eastern China were at the lowest risks of death, whereas infants in western China had the highest mortality. Several studies have reported a similar disparity of maternal, child, and neonatal mortality from eastern to western China (1)(2)(3)(20)(21)(22)(23). Overall, inadequate health service infrastructures and low health expenditure due to less developed economic status are thought to have resulted in inequity in neonatal and child health in the western region (2,23).…”
Section: Discussionmentioning
confidence: 98%
“…DAMA is a critical cause related to mortality in China ( 22 , 26 ). Our results identified that 17.7% of infants in western China were DAMA, the highest among all regions, contributing to the highest rate of overall mortality in western China.…”
Section: Discussionmentioning
confidence: 99%
“…While for infants ≤ 28 weeks, our LOS was approximately 10 days shorter compared with those reported by England and other 11 developed countries [ 9 , 25 ]. One possible explanation for shorter LOS in China may be relatively lower survival rates of infants with the smallest gestational age [ 27 ]. Greater survival in developed countries may result in more infants with morbidities associated with prolonged LOS.…”
Section: Discussionmentioning
confidence: 99%
“…NOD-, LRR-, and pyrin domain-containing protein 3 (NLRP3) inflammasome and its downstream Caspase 1, regulated the production of inflammatory molecules such as IL-1β ( 17 ), and miR-34a suppression reduces lung inflammation and apoptosis in an LPS-induced acute lung damage mouse model, indicating that miR-34a may mediate inflammasome activation ( 18 ). Except IL-1β, miRNA-34a also up-regulates TNF-α, IL-6, and Ang-1 production in animal or cell model ( 11 , 19 21 ), which all are proinflammatory factors that closed relate with progress of BPD. However, the dynamics of these pro-inflammatory cytokines during the development of BPD in preterm infants and their role in BPD have not been reported in detail.…”
Section: Introductionmentioning
confidence: 99%